PERFORMANCE LIMITS OF WIRELESS POWERED COOPERATIVE NOMA OVER GENERALIZED FADING - Nauryzbayev, Galymzhan; Omarov, Orken; Arzykulov, Sultangali; Rabie, Khaled M.; Li, Xingwang; Eltawil, Ahmed M. (Transactions on Emerging Telecommunications Technologies, 2021)
The non-orthogonal multiple access (NOMA) technique is a prospective solution to support the massive connectivity of an ever-increasing number of wirelessly connected devices and address the spectrum scarcity issue. In this article, the outage probability and ergodic capacity of a two-hop cooperative NOMA network with an energy-limited relaying node are quantified over a generalized 𝛼 − 𝜅 − 𝜇 statistical model. The relay acts in an amplify-and-forward mode and performs energy harvesting (EH) using the time-switching and power splitting relaying protocols. Moreover, the impact of hardware impairments (HIs) is incorporated into the performance evaluation. The obtained results prove the importance of HIs and allow one to evaluate the outage probability and ergodic capacity over various statistical models and system parameters. Finally, the results suggest that the optimal performance at a specific scenario depends on the combination of multiple factors, such as channel conditions, HI level, transmit power, and EH protocol.
Keywords: Type of access: Open Access; non-orthogonal multiple access (NOMA)